The Use of Video Media to Improve The Indonesian Language Learning Outcomes For Grade 1st Students - Munawaroh, Kunatun (Social, Humanities, and Educational Studies (SHEs): Conference Series, 2020)
The purpose of this study was to improve student outcomes in Indonesian language subjects in grade 1 elementary schools using video media learning models. The research conducted was a Classroom Action Research (CAR) in two cycles, with each cycle consisting of one meeting. The stages of each cycle are planning, implementing, observing and reflecting. Each meeting is carried out a pre test and post test to determine the progress of students. In the first cycle students who completed after carrying out the post test were 70%. In the second cycle students who completed after carrying out the post test were 85%. These results indicate that the learning model with video media can improve the learning outcomes of grade 1 students at SDN 1 Tanggulanom, especially Indonesian language muples.